Contradictions of the Practices of Consumption as the Specific Sources of Social Tension in the Contemporary Public Space - Lapina, Viktoria (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article substantiates the theoretical and practical significance of a sociological understanding of the contradictions of the practices of consumption as the specific sources of social tension in the contemporary public space of economic, political and sociocultural communications. It was emphasized that at the present stage of global and regional social transformations consumption is an important determinative factor of the value orientations by the population and becomes the specific subject-matter of scientific discussions both in Ukraine and abroad. The situation of conceptual uncertainty of the phenomenal and procedural features of the concept of «consumption», which reflects significant changes in the traditional views to consumption as one of the most important identification criteria of the social differentiation of society is analyzed by the author. The proofs of the scientific understanding of consumption as the fundamental civilization transcultural factor for providing organization and technological development of the contemporary production systems and as the effective resource exchange between individual and collective actors of public life are presented. It is argued that under conditions of the intensive global resource exchange, which caused by the activities of TNCs and by the processes of global human migration, the social influence of the new dysfunctional manifestations of consumption in the public space of the contemporary societies reflect the processes of real competition between different models of consumption and also reflect the increasing manipulative influence of mass media and of advertising as technological means of translation of values ideology of consumerism and the standards of elite consumption, without taking into account the existing deep social and economic inequalities in consumption practices by individual and collective actors. In the article is also proposed by the author the scientific research strategy which is oriented to understanding and studying the processes of intensification of the dysfunctional manifestations of consumption practices as the specific sources of social tension in order to develop effective managerial technologies for humanizing social life.